Gliricidia sepium intercropping for weed management in immature corn ear production - Tavella, Leonardo; Silva, Paulo Sérgio; Monteiro, Alex; Oliveira, Vianney; Fernandes, Patricia Liany (Revista Ciência Agronômica, 2017)
The goal of the study was to test the effects of combined weeding and gliricidia (Gliricidia sepium) intercropping for weed control in baby corn and green corn production. A completely randomized block design was employed, with split-plot and four replicates. Hybrids AG 1051 and BR 205 were subjected to the following treatments: A = two hoeings, 20 and 40 days after sowing (DAS); B = hoeing at 20 DAS + gliricidia intercropping following weeding; C = gliricidia intercropping established at the moment of corn sowing (GICS) + hoeing at 40 DAS; D = GICS; E = no weeding. Gliricidia was broadcast sown with 30 viable seeds m-2. The best treatments follow the order A > B > C as number of ears, fresh mass of ears with husks, fresh and dry masses of ears without husks for baby corn, and number of ears, fresh mass of ears with husks, fresh and dry masses of ears without husks for green corn. The worst results are observed for treatments D and E. Treatment D is only better than treatment E for the number of marketable ears without husks. No differences in the yields of immature ears exist between the hybrids.